PENGARUH EDUKASI KESEHATAN PERAWATAN KAKI TERHADAP PENGETAHUAN, SIKAP DAN PERILAKU PENCEGAHAN ULKUS KAKI DIABETIK - Johani dewita nasution; Sri Siswati; Dina Marnida Nasution (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2022)
Background: Patients with diabetes mellitus have a 15% risk of developing diabetic foot ulcers. Diabetic foot ulcers will not occur if people with diabetes have the knowledge and are willing to take care of their feet regularly. The purpose of this study was to determine the effect of health education on knowledge , attitude and prevention of diabetic foot ulcers . Method : Quasy experiment research design pre test - post test control group design. The sample was DM patients who visited the Muliorejo Health Center, the sampling technique was purposive sampling with a sample size of 20 people in the treatment group and 20 people in the control group. The independent variable is health education, the dependent variable is knowledge, attitudes and preventive measures for diabetic foot ulcers. Data collection by questionnaire. Data were analyzed using the Wilcoxon Sign Rank Test and the Mann-Whitney Test. Results : The results showed: there was an effect of health education on knowledge (p= 0.000), attitudes (p= 0.000) and actions (p= 0.000) in preventing diabetic foot ulcers. Discussion : Health education as an effort to persuade people with DM to be responsible for their health by first increasing their knowledge and attitudes. Future research should use more reliable but simple instruments to measure knowledge and avoid measurement bias.